2013
DOI: 10.1177/2048872613499282
|View full text |Cite
|
Sign up to set email alerts
|

IL-18 stimulates B-type natriuretic peptide synthesis by cardiomyocytesin vitroand its plasma levels correlate with B-type natriuretic peptide innon-overloadedacute heart failure patients

Abstract: This study provides the first evidence of the ability of IL-18 to induce B-type natriuretic peptide synthesis in vitro and outlines the relationship between the two molecules in acute HF patients with an ongoing inflammatory status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 45 publications
1
7
0
2
Order By: Relevance
“…Mallat et al 16 , found that there is no correlation between IL-18 and BMP levels in human heart failure, suggesting that they reflect different physiological mechanisms. On the other hand, DiSomma et al 19 discovered that IL-18 in view of its ability to exert inflammatory, hypertrophic and pro-fibrotic activities stimulates BNP synthesis by cardiomyocytes in vitro studies and correlates with BNP in non-overloaded acute heart failure patients, and in patient with heart failure, diabetes mellitus, and CAD. Moreover, Cordero-Reyes et al 20 , in their pre-clinical studies found positive correlations between BNP and IL-18 levels in patients with acute decompensated heart failure, suggesting a potential role of B-cells in their outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Mallat et al 16 , found that there is no correlation between IL-18 and BMP levels in human heart failure, suggesting that they reflect different physiological mechanisms. On the other hand, DiSomma et al 19 discovered that IL-18 in view of its ability to exert inflammatory, hypertrophic and pro-fibrotic activities stimulates BNP synthesis by cardiomyocytes in vitro studies and correlates with BNP in non-overloaded acute heart failure patients, and in patient with heart failure, diabetes mellitus, and CAD. Moreover, Cordero-Reyes et al 20 , in their pre-clinical studies found positive correlations between BNP and IL-18 levels in patients with acute decompensated heart failure, suggesting a potential role of B-cells in their outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Указывали на возможность стимуляции выработки BNP ангиотензином II, эндотелином-1 и катехоламинами [27,28]. В настоящее время в эксперименте и клинике убедительно продемонстрирована связь повышенного уровня провосполительного интерлейкина 18 и миокардиального синтеза BNP [29]. Получили подтверждение данных о возможной экспрессии гена, регулирующего синтез ВNP, под влиянием липополисахарида грамотрицательных бактерий [19].…”
Section: Discussionunclassified
“…55 An in vitro study revealed that IL-18 was associated with increased BNP. 56 In parallel, some studies indicated that inflammatory factors, such as neutrophil gelatinase-associated lipocalin, IL-6, and IL-18, were effective biomarkers to predict AKI non-recovery. 57-59 Together, these observations indicate that NT-proBNP is likely to have a strong correlation with CIN non-recovery, which leads to poor outcomes, and some factors, such as age, diabetes, proteinuria, and inflammatory factors, may contribute to this process.…”
Section: Follow-upmentioning
confidence: 99%